Flood hazard assessment using HEC-RAS mapping in Garyllis river basin, Cyprus - Kountouri, Josefina; Sigourou, Stavroula; Pagana, Vasiliki; Tsouni, Alexia; Panagiotou, Constantinos; Mettas, Christodoulos; Evagorou, Evagoras; Kontoes, Charalampos; Hadjimitsis, Diofantos (My University, 2024)
In recent years, there has been a noticeable escalation in both the frequency and severity of flood events around the globe, a situation exacerbated by climate change and human activities. This increasing trend is strongly connected with substantial risks to human lives, property, and cultural heritage, establishing floods among the most catastrophic natural disasters worldwide. This study is motivated by the necessity for effective flood management strategies to mitigate the growing risks. It focuses on assessing the spatial extent of flood events within Garyllis river basin in Cyprus, an area known to be highly susceptible to extreme weather events, being subjected to land use and land cover changes, and economic development. By adopting a comprehensive approach that combines modeling tools and techniques, such as remote sensing, Geographic Information Systems (GIS) and hydraulic modeling, together with multiple types of datasets and field observations, this research assesses flood hazards and projects their potential effects on the basin's residential, agricultural, and village areas. This study utilizes the open-source HEC-RAS software to simulate the spatio-temporal evolution of surface water depths during a hypothetical 24-hour flood event with a 1,000-year recurrence interval, revealing the presence of high-risk regions located at the southern part of the catchment area close to the urban area. The results provide insights for policymakers and urban planners to design effective flood mitigation strategies, aiming to lessen the adverse effects of floods on communities and economic activities.
Keywords: Flood hazard; flood vulnerability; HEC-RAS; Garyllis river basin